Design And Fabrication Of A Tropical Motorcycle Helmet - Shuaeib, Farag Mohamed (2003)
The present work is devoted to the design and evaluation of a new crashworthy motorcycle helmet taking into consideration the tropical climate of Malaysia. A multidiscipline literature review on the design problems of motorcycle helmet was carried out and current problems were formulated. Based on the literature review findings, a new shell and liner designs were then proposed to overcome or eliminate these problems. The shell design improvements consisted of developing hybrid natural fiber composite (NFC) shells which were fabricated and evaluated by the standard dynamic penetration test. The results of the new design were found to be satisfactory according to the related helmet standards. Three additional methods have been developed to assess the new shells performance in a more quantified manner. These tests are the helmet quasi-static penetration, the helmet rigidity, and the helmet crushing. All these tests were performed and the results confirmed the superior performance of the new natural fiber shell helmets as compared to the market dominant ABS shell helmets. Other factors also supported this design improvement such as cost, and the utilization of environmental friendly material. In the liner design improvement, the shell was kept to the current ABS shell and the EPP foam as a liner. A 3D finite element algorithm has been developed using LSDYNA- 3D software. Based on the simulation results, the helmet with EPP foam liner was found to be satisfactory according to the related helmet standards. A parametric study of the helmet design was performed using the Response Surface Methodology in the Design of Experiment (DOE) statistical method. From this parametric study, the foam thickness and the foam density were found to have more significant effect on the helmet energy absorption than the she]] effects. Design optimizations were also conducted and optimum design was obtained. Finally, thermal analysis for commercially available helmet without ventilation system and the new helmet design with ventilation system were made. from which it was found that helmet ventilation is essential to avoid possible health problems. A design chart for helmet with ventilation system to obtain the minimum cross sectional area required for ventilation nozzles has been developed. This chart is suitable for a wide span of amounts of heat generated from the motorcyclist head. The effect of adding the ventilation system to the helmet has been structurally investigated by the finite element simulation and found to positively improve the energy absorption performance of the helmet.